Pola Penggunaan Kombinasi Dua Obat Antihipertensi pada Pasien Hipertensi - Tri Wulandari (STIKES Karya Husada Kediri, 2019)
Hypertension is a longlife disease. A study of the combination of two antihypertension medicine used in outpatient polyclinic of Hospital Surakarta. The purpose of this study is to know the description of two combination antihypertensive medicine therapy and effectiveness therapy. This research is a non experimental, description design, retrospective data from medical records. The study population is hypertension stage 2 in outpatient polyclinic. Sample collection technique with purposive sampling, the inclusion criteria of the diagnosed stage 2 hypertension, age ≥18 years, and combination therapy for the first time up to 4 months. The variable pattern of hypertension combination and the effectiveness therapy. The was 64,6% of female because by hormonal changes in female, the highest age ≥ 60 years is 63,4% the age range changes in the elasticity of bloods wall. The highest systole blood pressure 160-180 mmHg, diastole 90-100 mmHg. The combinations of classes, and the most widely used is Calcium Cannel Blocker- Angiotensin II Receptor Blocker of 36.6% and effectiveness of 86.7%. The conclusion in this study the two most effective antihipertention drugs is CCB + ARB.